Pengaruh Fasilitas Dan E-Wom Terhadap Keputusan Berkunjung Di Daya Tarik Taman Nirwana Sungai Barameh Kota Padang - Restiyani Restiyani; Nidia Wulansari (Lembaga Pengembangan Kinerja Dosen, 2023)
The research was conducted against the background of visitor complaints on social media about tourist facilities. The goal of this study was to determine how visitor decisions at Padang City's Barameh River Nirwana Park attraction were influenced by tourist amenities and E-WOM. With a causal associative methodology, the research is descriptive and quantitative. Population criteria are visitors who have visited Taman Nirwana, have seen reviews about Taman Nirwana on social media and visitors over 20 years old. Purposive sampling was used to collect 120 respondents. Data was collected from questionnaires that have been tested valid and reliable.. Multiple linear regression tests were used to test the research hypothesis with the help of SPSS 23.00, obtaining the results, namely: (1) Tourist Facilities with adequate category (38%), electronic word of mouth with adequate category (39%) and Visiting Decision with adequate category (41%). A significant value of 0.000 <0.05 is assigned to the estimated F score of 63.875. This indicates that the effects of X1 and X2 on Y are significant. This means that the hypothesis (H3) is accepted X1, X2 simultaneously affect Y, then the regression coefficient value for variable X1 is 0.268 with a significance value of 0.000 <0.05 and variable X2 is 0.293 with a significance value of 0.013 <0.05. This means that every 1 unit increase in tourist facilities will increase 0.268 visiting decisions and every 1 unit increase in E-WOM will increase 0.293 visiting decisions. Then the Adjust R square value of 0.514 is obtained, which means that the effect of variables X1 and X2 on Y is 51.4%, while 48.6 is influenced by other factors. so it can be concluded in this study that Ha is accepted